Development of Antibacterial Fabrics by CuO Doped TiO2 Composites - Kristianto, D.; Ibadurrohman, M.; Slamet (Asian Journal of Chemistry, 2021)
The study aimed to get the optimum antibacterial properties on fabric. CuO-doped TiO2 composite was synthesized by photo assisted deposition method. The amount of CuO loading varied (1.5%, 3% and 6%) in the total weight of composite to obtain the optimum effect of CuO in photodisinfection Escherichia coli. The 3% CuO/TiO2 possessed the optimum antibacterial activity with 92% of E. coli were disinfected within 2 h. This phenomenon was supported by the UV-Vis DRS results, which implied the addition of CuO could act as a dopant and an electron trapper in reducing the band-gap energy to 2.97 eV in 3% CuO/TiO2. Fourier-transform infrared spectroscopy (FTIR) analysis showed the Ti-O-Ti and Ti-O-Si bands, which confirmed TiO2 attach on fabric.